Criminal acts of manipulation of electronic information in order to get free fashion on online transactions - Jusnizar Sinaga; Jinner Sidauruk; Sonya Batubara (Institute Of computer Science (IOCS), 2023)
Mobile phone is a technology used to facilitate human work, and over time the mobile phone has many functions that ultimately led to many social changes in society that change their behavior in interacting with other humans and continue to spread to other parts of human life, so that there are new norms, new values, and so on. As for the problems in this study is the conviction and consideration of the judge in passing a verdict against the perpetrators of manipulation of electronic information in order to get free fashion on electronic transactions study Decision No.6/Pid.Sus/2021 / PN.BDG. The type of research used in this study is normative juridical research, namely research used by analyzing library materials, one of which is Decision No.6/Pid.Sus/2021 / PN.BDG. It can be concluded that Vinna and her sister Vivie make online transactions by buying fashion (clothing) from the “Giordano online store” by way of payment using proof of transaction that has been edited using the adope photoshop application so that it is as if the proof of transfer used is original, then based on the facts of the trial obtained from the testimony of, the information of the defendants and the evidence submitted in the trial then the action is proven to violate the provisions of Article 51 juncto Article 35 of the law of the Republic of Indonesia number 19 of 2016 concerning amendments to the law of the Republic of Indonesia number 11 of 2008 concerning information and Electronic Transactions juncto Article 64 paragraph 1 of the Criminal Code juncto Article 55 paragraph 1 to-1 of the criminal code so that it can be convicted.